Artificial Intelligence in Pediatric Dentistry - Shakya, Raju Raj (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Dentistry has evolved through a long journey. The incorporation of Artificial Intelligence (AI) is the present and future of dentistry. Artificial Intelligence is now gradually being used in various fields including medical healthcare and dentistry. Within the field of dentistry, Pediatric dentistry requires skills to perform procedures with proper patient behavior guidance skill. The present article aims to highlight the various AI innovations and its relation to pediatric dentistry with possible future supported with Robotics which might change the traditional way of clinical practice.